The Implementation of Trivial Pursuit media to Improve students’ Nahwu Result at Darussalam Islamic Boarding School Tasikmalaya - Wahyudi, Muhammad; Rahmawati, Rina Dian; Mulyanto, Dedi; Fauziah, Hana (UAS PRESS, 2025)
Darussalam Islamic Boarding school Tasikmalaya is an integrated curriculum that includes Salafiyah, KMI Gontor, Tahfidz and Kemendikbud programs to develop students proficient in Arabic and English. However, challenges like lack of student attention during lessons, due to ineffective teaching media, have affected learning outcomes. This study aimed to implement Trivial Pursuit educational media to increase student engagement and improve learning outcomes in the Nahwu subject for class 5C. The research applied Classroom Action Research (CAR) based on Kurt Lewin’s model, including planning, implementation, observation, and reflection. Data were gathered through interviews, observations, tests, and documentation. Results showed that using Trivial Pursuit increased student participation from 80% to 90%, and learning outcomes improved from 60% to 100%. Students are encouraged to become more active and Nahwu teachers are recommended to use more effective teaching methods. The pesantren is also advised to enhance the use of teaching strategies and media.